Quantum Mechanics Approach for Metal-Organic Frameworks Deformation Effect on Carbon Capture Performance: A Density Functional Theory Study - Muhdi, Krisna Dwipa; Fikri, Ahmad Atif (Journal of Mechanical Engineering, Science, and Innovation, 2025)
Increasing carbon dioxide (CO₂) emissions from fossil fuel combustion demand the development of effective and efficient carbon capture technologies. Metal-Organic Frameworks (MOFs) are excellent candidates as adsorbent materials because they have uniform pores, specific surface area, and can modified according to purpose. However, performance of MOFs may decrease due to structural deformation during  adsorption-desorption process, especially under extreme conditions. This study uses a quantum mechanical approach, namely Density Functional Theory (DFT), to analyze effect of deformation, specifically hMOF-13, on its performance in CO₂ adsorption. Through modeling the atomic structure of hMOF-13, an understanding of the quantum interactions between atoms, changes in position of atoms and cells due to deformation is obtained. Simulation results show that mechanical deformation of hMOF-13 decreases CO₂ adsorption performance through pore narrowing and electrostatic charge redistribution. In addition, excessive deformation can trigger structural failures that reduce regeneration cycles and lower carbon capture efficiency. Insights from this study can guide the subsequent development of MOFs with enhanced mechanical resistance, contributing to the optimization of industrial-scale carbon capture processes. By improving the structural stability of MOFs, industries can achieve higher adsorption efficiency, longer material life, and reduced operational costs, making carbon capture technology more feasible and sustainable.